The Evolution of Islamic Educational Institutions in Indonesia - Asmanto, Budi; Suradi, Suradi; Warisno, Andi; Andari, An An; Anshori, M Afif (Graduate Program Magister Manajemen Pendidikan, 2023)
The aim of this library research is to describe the history of Islamic educational institutions in Indonesia. The instrument in this study is documentation of literatures. The study found that the educational institutions are a strategic tool for the process of transforming values and culture in a social community. The existence of Islamic educational institutions cannot be separated from the process of the arrival of Islam in Indonesia. The emergence of Islamic educational institutions in a community does not experience a vacuum, but is always dynamic, both in terms of function and learning. The presence of Islamic educational institutions has provided its own spectrum in opening insights and intellectual dynamics of Muslims. Islamic educational institutions have experienced a long history. The study concluded that Islamic educational institutions cannot be separated from the history of Islamic education. Islamic education in Indonesia is as old as the existence of Islam in the archipelago.